Threats to Established Companies from Increasing Digitalization (European Journal of Marketing and Economics, 2021)
In today's world, companies have to deal more than ever with increasing globalization/internationalization and enormous competitive pressure. Strong competitive pressure leads to faster and faster innovation cycles, constant technical innovations and programmes for further cost reductions. In recent years, digitalization has added another challenge for established companies. New competitors are blurring industry models through digitalization and offerings based on disruptive innovation, proven business models are no longer suitable from one day to the next and established companies are competing with service or usage offerings. Such service or usage offerings will almost always be considered by the millennial or always-on generation and pose significant risks to established companies.
Keywords: Disruptive Innovation, digitalization, risks to established companies